Influence of the oxide–semiconductor interface on the resistive switching phenomenon in metal/Al2O3/InGaAs - Palumbo, Félix Roberto Mario (2014)
In this work, the influence of the oxide–semiconductor interface on the resistive switching phenomenon was studied in metal gates /Al2O3/InGaAs structures. Different sets of samples were manufactured to produce different qualities of oxide–semiconductor interfaces. The influence of the Al2O3/InGaAs interface on the resistive switching effect was studied by combining electrical characterizations with an analysis of the composition of the oxide/semiconductor interface. The results suggest that a low surface quality results in a decrease of the damage on the conductive filament responsible for the transitions between two resistive states.